A cohort study of blunt cerebrovascular injury screening in children: Are they just little adults?. Issue 1 (January 2018) - Cook, Mackenzie R.; Witt, Cordelie E.; Bonow, Robert H.; Bulger, Eileen M.; Linnau, Ken F.; Arbabi, Saman; Robinson, Bryce R.H.; Cuschieri, Joseph
Abstract : BACKGROUND: Blunt cerebrovascular injuries (BCVIs) are rare with nonspecific predictors, making optimal screening critical. Radiation concerns magnify these issues in children. The Eastern Association for the Surgery of Trauma (EAST) criteria, the Utah score (US), and the Denver criteria (DC) have been advocated for pediatric BCVI screening, although direct comparison is lacking. We hypothesized that current screening guidelines inaccurately identify pediatric BCVI. METHODS: This was a retrospective cohort study of pediatric trauma patients treated from 2005 to 2015 with radiographically confirmed BCVI. Our primary outcome was a false-negative screen, defined as a patient with a BCVI who would not have triggered screening. RESULTS: We identified 7, 440 pediatric trauma admissions, and 96 patients (1.3%) had 128 BCVIs. Median age was 16 years (13, 17 years). A cervical-spine fracture was present in 41%. There were 83 internal carotid injuries, of which 73% were Grade I or II, as well as 45 vertebral injuries, of which 76% were Grade I or II, p = 0.8. More than one vessel was injured in 28% of patients. A cerebrovascular accident (CVA) occurred in 17 patients (18%); eight patients were identified on admission, and nine patients were identified thereafter. The CVA incidence was similar in those with and without aspirin use. The EAST screening missed injuries in 17% of patients, US missed 36%, and DC missed 2%. Significantly fewer injuries would be missed using DC than either EAST or US, p < 0.01. CONCLUSIONS: Blunt cerebrovascular injury does occur in pediatric patients, and a significant proportion of patients develop a CVA. The DC appear to have the lowest false-negative rate, supporting liberal screening of children for BCVI. Optimal pharmacotherapy for pediatric BCVI remains unclear despite a relative high incidence of CVA. LEVEL OF EVIDENCE: Diagnostic study, level III.